2020
DOI: 10.1021/acs.jafc.9b07391
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic “Turn-On” Aptasensor Detection of Ochratoxin A Using Energy-Transfer Fluorescence

Abstract: Ochratoxin A (OTA) is an intrinsically fluorescent phenolic mycotoxin that contaminates a wide range of food products and is a serious health threat to animals and humans. An OTA binding aptamer (OTABA) that folds into an antiparallel G-quadruplex (GQ) in the absence and presence of target OTA has been incorporated into a vast variety of aptasensor platforms for OTA detection. The development of a simple, aptamer-based approach would allow for detection of the toxin without the use of complex analytical instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The fluorescence turn-on response was further increased to ∼10-fold using energy-transfer (ET) fluorescence (Figure A). ET fluorescence between DNA (donor) and a fluorescent chromophore (acceptor) occurs when acceptor binding involves π-stacking interactions, which permits energy of UV absorbance by DNA base pairs to be efficiently transferred to the ground-state fluorescent probe to cause excitation to furnish a turn-on emission response. , ET fluorescence within GQ structures provides ET efficiencies that are higher than duplex-to-probe examples , because the central metal ion promotes polarization enhancement (Figure B) of donor G-residues to furnish greater enol character (like O 6 -methylG, which is more emissive than its keto counterpart). Interestingly, the excitation wavelength for the Pb 2+ -bound TBA sample displayed a noticeable shift to the red compared to the K + -bound sample for a maximum wavelength change at 310 nm (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence turn-on response was further increased to ∼10-fold using energy-transfer (ET) fluorescence (Figure A). ET fluorescence between DNA (donor) and a fluorescent chromophore (acceptor) occurs when acceptor binding involves π-stacking interactions, which permits energy of UV absorbance by DNA base pairs to be efficiently transferred to the ground-state fluorescent probe to cause excitation to furnish a turn-on emission response. , ET fluorescence within GQ structures provides ET efficiencies that are higher than duplex-to-probe examples , because the central metal ion promotes polarization enhancement (Figure B) of donor G-residues to furnish greater enol character (like O 6 -methylG, which is more emissive than its keto counterpart). Interestingly, the excitation wavelength for the Pb 2+ -bound TBA sample displayed a noticeable shift to the red compared to the K + -bound sample for a maximum wavelength change at 310 nm (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…For the internally modified 4QI–TBA 16 sample (solid red trace), λ ex /λ em was observed at 510/581 nm, and the internal dye displayed an impressive 40.6-fold increase in intensity compared to free 4QI and 10.9-fold greater than label-free 4QI/TBA 16 . The excitation spectrum also displayed a prominent ET band at 256 nm, confirming strong π-stacking interactions between the internal 4QI surrogate and the GQ structure. , This observation suggested that favorable π-stacking interactions between 4QI and DNA base pairs accounted for the relatively small Δ T m values for duplex and GQ structures produced by 4QI–TBA 16 compared to the native strand (Table ).…”
Section: Resultsmentioning
confidence: 78%
“…A simple detection method based on the unique antiparallel G4 structure formed by OTA was reported (Armstrong-Price et al, 2020 ). The “turn-on” fluorescence self-signal (λ ex /λ em = 256/425 nm) is generated by π-stacking interactions that lead to G4-to-toxin energy transfer (ET).…”
Section: G-quadruplex-based Detection Methods For Otamentioning
confidence: 99%